Design of Temporary Storage Sites (TPS) for B3 Waste in the Water Tourism Sector in Malang Regency: Perencanaan Tempat Penyimpanan Sementara (TPS) Limbah B3 pada Sektor Wisata Air di Kabupaten Malang - Ragil Prastyo; R. Mohammad Alghaf Dienullah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The growth of the water tourism sector in Malang Regency has resulted in an increase in the generation of Hazardous and Toxic Materials (B3) waste, which threatens the sustainability of aquatic ecosystems. This study presents a representative design for a Temporary Storage Facility (TPS) for B3 Waste that complies with environmental safety technical standards. The study methods used include waste characteristic identification, direct weighing sampling, and engineering design based on the compatibility principle. The evaluation results indicate a total B3 waste generation of 23.35 kg/month, with the largest contribution coming from used battery waste (A102d) of 8 kg/month. Based on this data, a TPS facility with dimensions of 7.5 m x 3.5 m x 3.5 m was designed, equipped with a natural ventilation system, emergency drainage channels, and a spill pallet. The planning of this facility serves as a prototype for mitigating environmental pollution risks to ensure regulatory compliance in water tourism areas.